Sita in Cultural Translation The Use of the Rāmāyana to Educate on Perfect Womanhood by Annie Besant, Marie Musaeus Higgins, and Leelawathy Ramanathan - Albrecht, Jessica (Medical Humanities, 2023)
It is no longer a novelty in Religious Studies that translations play an integral role in questions of (inter-)cultural contact, comparison, and identity. But the question of what translation means, how it relates to interpretation, and the role of text, language, and practice has not been adequately addressed. In recent years, feminist historical research has published some ground-breaking work addressing this very question. This article uses a cross-disciplinary (literature studies, feminist translation studies and religious studies) approach to examine four different Ramayana versions in late colonial Ceylon and India (1900–1930) written by the Theosophists Annie Besant, Marie Musaeus Higgins and Leelawathy Ramanathan for the purpose of girls’ education. The differing portrayals of Sita as the “perfect wife” will be used to highlight the importance of theories of translation for the study of global religious history.
Created from Fastlane, Scopus look-up
Keywords: colonialism; feminist translation; gender history; global religious history; Ramayana; Sri Lanka